2014
DOI: 10.1007/s10552-014-0459-2
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D status and risk of non-Hodgkin lymphoma: a meta-analysis

Abstract: Higher vitamin D status does not play a protective role in risk of NHL or common NHL subtypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 57 publications
1
11
0
Order By: Relevance
“…The positive association between higher vitamin D levels and the incidence of non‐Hodgkin lymphomas is corroborated by a recent meta‐analysis in finding no protective effect of higher vitamin D levels in relation to the risk of developing non‐Hodgkin lymphoma. Several cancers are associated with immune suppression, and non‐Hodgkin lymphomas occur more often in patients with non‐melanoma skin cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The positive association between higher vitamin D levels and the incidence of non‐Hodgkin lymphomas is corroborated by a recent meta‐analysis in finding no protective effect of higher vitamin D levels in relation to the risk of developing non‐Hodgkin lymphoma. Several cancers are associated with immune suppression, and non‐Hodgkin lymphomas occur more often in patients with non‐melanoma skin cancer.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that vitamin D deficiency or sunlight-mediated immune modulation may play a role in non-Hodgkin lymphomagenesis [64]. Although a recent meta-analysis did not confirm a protective role for vitamin D in NHL[65], there is evidence that vitamin D deficiency may adversely impact NHL treatment and/or survival. In a Norwegian population-based study investigating the relationship between 25-hydroxyvitamin D levels and risk of death in cancer patients, higher levels were associated with superior survival in 145 patients with lymphoma [66].…”
Section: Preventive and Therapeutic Implicationsmentioning
confidence: 99%
“…Diets high in trans-fatty acids, processed meats, and higher fat dairy products were positively associated with NHL risk; whereas diets high in n3 fatty acids and total seafood were inversely associated with risk (4). In a meta-analyses conducted from 9 studies (8 case-control and 1 cohort), it was reported that higher vitamin D status does not play a protective role in risk of NHL or common NHL subtypes (6). Several studies have also shown diet to be associated with inflammation(11, 12).…”
Section: Discussionmentioning
confidence: 99%
“…Infections with HIV, hepatitis B (HBV) and C (HCV) viruses, Epstein-Barr virus (EBV), human herpes virus 8, and perhaps Helicobacter pylori are among the few established risk factors for specific NHL histological subtypes (3). There also is growing evidence indicating a possible role of diet in the development of NHL (46). Increased trans-fatty acid intake was associated with increased risk, whereas increased omega-3 fatty acid intake was associated with decreased NHL risk (4).…”
Section: Introductionmentioning
confidence: 99%